ECONOMIC EMPOWERMENT IN SIDOARJO YATIM MANDIRI LAZNAS THROUGH BUNDA CAN PROSPERITY (BISA) - Ali Hamdan; Nur Mala Hayati (Ekosiana Jurnal Ekonomi Syari ah, 2017)
ABSTRACT The increasing number of births in an area that is not balanced by the increasing number of production will be a serious problem for a country. And to overcome the problem of poverty, one of them is the existence of a Community Empowerment program. Based on this, the authors formulated the problem in this study about how economic empowerment in orphaned LAZNAS can be implemented and also how the results of this economic empowerment.The purpose of this study was to find out how economic empowerment at the Yatim Mandiri LAZNAS through this BISA mother program could be carried out and also to find out the results of this economic empowerment. The object in this study was LAZNAS Yatim Mandiri Sidoarjo, while the subject was Mother CAN.The results of this study indicate that the utilization of LAZNAS funds towards the Bunda Bisa Sejahtera program (BISA). In addition to providing assistance in the form of venture capital funds, Yatim Mandiri also provides guidance on entrepreneurship and also spiritual development with the aim of strengthening faith and also changing the pattern of thinking to become entrepreneurs who have a good spiritual spirit. To become a member of CAN, the CAN program will not only receive rotating funds but also receive monthly donations for their daily needs of IDR 50,000 per mother, which can be in the form of basic food worth fifty thousand rupiahs, to help ease the daily needs. orphaned mother's day.The results of this study indicate that the utilization of LAZNAS funds towards the Bunda Bisa Sejahtera program (BISA). In addition to providing assistance in the form of venture capital funds, Yatim Mandiri also provides Keywords: Empowerment, Laznas, Mother of Orphan